Family Genomoviridae: 2021 taxonomy update - Varsani, Arvind; Krupovic, Mart (Archives of virology, 2021)
The family Genomoviridae (phylum Cressdnaviricota , class Repensiviricetes , order Geplafuvirales ) includes viruses with circular single-stranded DNA genomes encoding two proteins, the capsid protein and the rolling-circle replication initiation protein. The genomes of the vast majority of members in this family have been sequenced directly from diverse environmental or animal- and plant-associated samples, but two genomoviruses have been identified infecting fungi. Since the last taxonomic update of the Genomoviridae , a number of new members of this family have been sequenced. Here, we report on the most recent taxonomic update, including the creation of one new genus, Gemytripvirus , and classification of ~420 new genomoviruses into 164 new species. We also announce the adoption of the “Genus + freeform epithet” binomial system for the naming of all 236 officially recognized species in the family Genomoviridae . The updated taxonomy presented in this article has been accepted by the International Committee on Taxonomy of Viruses (ICTV).